Fresh and hardened properties of recycled plastic fiber reinforced self-compacting concrete made with recycled concrete aggregate and fly ash, slag, silica fume. (15th December 2022) - Dong, Chunru; Zhang, Qingyang; Chen, Chuan; Jiang, Tianxun; Guo, Zhanggen; Liu, Yi; Lin, Shanli
Abstract: This study addressed the issue of recycling of waste plastic, industry by-products and waste concrete into sustainable concrete materials, which aims to produce a green and environmental-friendly self-compacting concrete (SCC). A novel and sustainable approach was proposed by combined inclusion of supplementary cementitious materials (SCMs) and recycled plastic fibers (RPFs), which was expected to improve the workability, mechanical properties and durability of recycled aggregate SCC (RA-SCC) simultaneously. This study firstly presents a deep insight into the benefits of the coupling effect of waste plastic fibers and SCMs on the fresh and hardened properties of recycled aggregate SCC mixes. Four series, 17 RPF reinforced RA-SCC (RPF-RA-SCC) were prepared by substantially substituting natural aggregates with recycled concrete aggregates and cement with SCMs, as well as reinforced with RPFs resulting from cutting waste plastic bottles. Fresh properties, including filling ability, cohesiveness, passing ability, segregation resistance and hardened properties, in terms of compressive, elastic modulus and flexural strength were measured. The effect of RCA content (50%, 100%), SCM content (50%, 75%) and different combination type, RPF content (0.5%, 1.0%, 1.5%) on the fresh and hardened properties of RA-SCC mixes was analyzed. The coupling effect of RPFs and SCMs was analyzed in detail. Microstructure analysis using scanning electron microscope (SEM) was conducted to study the microstructure characteristic. The test results indicated that the addition of RPFs impaired the workability. However, the inclusion of SCMs greatly improved the fresh properties and all RPF-RA-SCC mixes exhibited superior workability. The combined addition of RPFs and SCMs resulted in an excellent coupling effect and leaded to a notable improvement on the mechanical properties. The benefits of combined addition of SCMs and RPFs are higher than the sum of the benefits obtained through individual inclusion of SCMs and RPFs. Highlights: A sustainable approach was proposed by combined inclusion of SCMs and waste plastic fibers. Fresh and hardened properties were simultaneously improved by combined addition of SCMs and waste plastic fibers. The addition of SCMs increased the pull-out and bond strength of waste plastic fibers. Combined addition of RPFs and SCMs result in excellent coupling effect. Combined addition of RPFs and SCMs result in additional improvement in the net gain.